APPLICATION OF INNOVATIVE INFORMATION TECHNOLOGIES IN TRADE OPERATIONS MANAGEMENT - BOKOVETS, Viktorііa; NETREBSKYY, Vadym; KANASHCHUK, Maksym; MALEVYCH, Denys (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Innovative information technologies are becoming increasingly essential to support competitiveness in the modern business world. This article examines the importance of their implementation in managing trade operations and their impact on enterprises.Some of the key innovative technologies used in this field include advanced data analytics, artificial intelligence, blockchain, and the Internet of Things (IoT). They help optimize management processes, ensure secure transactions, and enhance supply chain efficiency.Assessing the level of implementation of these technologies in enterprises plays a crucial role in determining their competitiveness. Some companies successfully integrate advanced solutions, while others encounter obstacles such as budget constraints or technological limitations.Analyzing technology trends helps businesses adapt to market changes and develop strategies according to new opportunities. Understanding and anticipating future technological developments are key to successful adaptation.Innovative information technologies play a significant role in managing trade operations. Understanding their potential and proper implementation can help enterprises succeed in the modern business environment.In addition to their role in enhancing operational efficiency and competitiveness, innovative information technologies also offer opportunities for improving customer experiences and expanding market reach. Through personalized marketing strategies, real-time customer engagement, and seamless online transactions, businesses can create more value for their customers and build stronger relationships.
Keywords: innovations; information technologies; trade operations; competitiveness; data analytics; artificial intelligence; blockchain; IoT